Not enough Sami? The affects of postcolonial identity - Starkutė, Ugnė Barbora (Lietuvos etnologija / Lithuanian ethnology, 1557)
The article explores how people identify with their ‘Saminess’. To understand this better, discourses of affects and emotions around the topic are analysed, particularly shame and inadequacy. They show how people ‘measure’ Saminess in relation to ‘proper’ Sami. I investigate here if this is a fault of a discursive dichotomy between modernity and tradition – the depiction of a traditional indigenous group forming in opposition to a coloniser’s modern identity. Čia analizuojami su samiškumu siejami afektų ir emocijų diskursai, tiksliau, gėda ir nepakankamumo jausmai, kurie atskleidžia, jog žmonės „matuoja“ savo samiškumą lygindamiesi su „tikru samiu“. Straipsnyje atskleidžiama, kad tai yra vyraujančių modernybės sukurtų dichotomijų pasekmė, kai kolonizatorius siejamas su modernybe, o autochtoniškumas – su tradicija.